Socio-ecological factors in talent development in cricketers in a diverse society - Dove, Mary Ann (Division of Exercise Science and Sports Medicine, 2019)
Introduction: In recent years, there has been a move to understand the environment and context in which athletes develop. South Africa’s unique context provides an opportunity to understand how environmental factors could influence talent development in cricket. Since democracy, there has been limited representation of Black African cricketers at the elite levels in South Africa. Therefore, the aim of this thesis was to determine the role that socio-ecological factors may play in the development of cricket talent in a diverse society. Methods: Qualitative research methods were used to explore the experiences and perceptions of South Africa’s male cricketers as they progressed through the talent pathway from exposure to the game to the elite level. The perceived effectiveness of the introduction of an ethnic target policy was also explored. Seventy-one semi-structured interviews were conducted with a purposive sample of players from all ethnic groups (n=43), and with knowledgeable and experienced key informants (n=16). A thematic analysis of the data resulted in the identification of themes which are presented using a multi-level socio-ecological framework. Results: All players progressed to the elite level; however, their access points to and routes through the pathway varied. This progress was influenced by the inter-relationship of distal and proximal socio-ecological factors that they experienced during their cricketing careers. These influences can be summarised into five talent development components that acted either as barriers or enablers to progress: (1) access to opportunities and competition, (2) holistic player development, (3) effective support networks, (4) inclusive team environments, and (5) adaptive mind-sets. In addition, various intrapersonal characteristics were identified that further affect a player’s ability to achieve elite cricketing success. Finally, it was determined that an ethnic target policy alone is not an effective intervention for developing cricket talent in a diverse society undergoing transition. Conclusion: A socio-ecological framework to talent development lends additional support to the idiosyncratic, multifactorial, dynamic and complex way in which cricket expertise is achieved, particularly in diverse societies. It provides stakeholders involved in the talent development process with evidence to inform policy and practice, as well as design effective interventions.